Mercury pollution in the soil and river water of the Ratai watershed by artisanal and small-scale gold mining activities in Pesawaran District, Lampung, Indonesia - Slamet Budi Yuwono; Irwan Sukri Banuwa; Nano Suryono; Hiroaki Somura; Dermiyati Dermiyati (Brawijaya University, 2023)
The high risk of mercury pollution in the Ratai watershed due to artisanal and small-scale gold mine activities in Pesawaran District, Lampung, Indonesia, was evaluated. Studies are needed to improve the understanding of the effect of heavy metal pollution, especially mercury (Hg), in soil and river water along the watershed because of erosion. The Universal Soil Loss Equation (USLE) integrated with Geographic Information Systems (GIS) model was used to analyze the transport of mercury (Hg) from nonpoint source pollution loads to the Way Ratai River using rainfall-based erosion. Soils and river water samplings were conducted in 2020. Biophysical conditions, the land cover, and the rainfall data of the Ratai watershed were also taken into account. The results indicated that Hg concentrations in the soil and the river water were high, ranging from 0.26-28.9 mg L-1 and from 0.08-14.1 mg L-1, respectively. The reason for the high Hg contents in the soils and the river waters was the high erosion rate in the watershed. As the study area was characterized by high rainfall erosivity and low to high soil erodibility, the erosion-caused Hg contamination in soil and water can be significant if no conservation strategies are developed.